SCRUTINIZING THE STATUS OF FRANCISCAN APOSTOLIC SISTERS SCHOOLS - LABRADOR FAS, SR. ELLEN S. (International Journal of Arts, Sciences and Education, 2024)
The purpose of this study is to provide a full overview of the educational landscape of schools that are linked with the Franciscan Apostolic Sisters. The study conducts a thorough examination of the current situation of these institutions. The research investigates a wide range of aspects, including infrastructure, academic performance, faculty competence, and extracurricular activities, by conducting an in-depth analysis of each of these aspects. The purpose of this study is to identify the strengths, problems, and potential areas for growth that are present inside these educational institutions by adopting a multidimensional approach of investigation. Within the Franciscan Apostolic Sisters, it is anticipated that the findings will provide useful insights that will drive strategic decisions, policy formulation, and efforts that are aimed at increasing the overall educational quality and effect of their schools. This research is significant not only for the internal evaluation of these schools but also for the larger educational community as a whole. It provides a nuanced view on the current situation of Franciscan Apostolic Sisters schools in the context of the contemporary educational landscape.